Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1080/14622200410001669178
|View full text |Cite
|
Sign up to set email alerts
|

So near, yet so far: Tobacco dependence treatment for pregnant women

Abstract: Almost one-half million babies in the United States are born yearly to women who report smoking while pregnant. Almost all of these pregnant women have access to prenatal care, through federally financed health clinics, state and county health programs, or private providers. However, many pregnant smokers are unlikely to receive any type of counseling or assistance to help them stop smoking--despite the availability of evidence-based treatment and the considerable return on investment. This article recommends … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…This study supports the importance of system‐based interventions in adhering to clinical practice guidelines. The guidelines recommend the utilization of system‐based interventions 13 to improve tobacco dependence treatment, and other studies have demonstrated the benefits of utilizing office‐based strategies 36,37 . Tobacco cessation treatment should be viewed within the context of quality improvement and thus include targeting the entire practice environment, as well as including all practice clinicians and staff in participating in tobacco cessation treatment training.…”
Section: Discussionmentioning
confidence: 99%
“…This study supports the importance of system‐based interventions in adhering to clinical practice guidelines. The guidelines recommend the utilization of system‐based interventions 13 to improve tobacco dependence treatment, and other studies have demonstrated the benefits of utilizing office‐based strategies 36,37 . Tobacco cessation treatment should be viewed within the context of quality improvement and thus include targeting the entire practice environment, as well as including all practice clinicians and staff in participating in tobacco cessation treatment training.…”
Section: Discussionmentioning
confidence: 99%
“…18 A suggested model for comprehensively addressing this goal for pregnant women includes: support from top leadership in the health organisation; clinical information systems to track individual patient information; ongoing training of providers and staff; the assignment of specific staff to provide smoking cessation counselling; innovative support systems for smokers trying to quit; and community support. 18 Increasing each state's capacity to deliver smoking cessation interventions needs to address the barriers that exist at the level of the prenatal provider. 11 14 30 Something as essential as a provider's awareness of changes in reimbursement for coverage needs to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…13 Reimbursement for smoking cessation interventions during pregnancy is promoted as an important step to address key provider and system level barriers. [15][16][17][18][19] Recommendations for reimbursement are based on proven effectiveness of smoking cessation interventions 11 19 20 and evidence that they are cost effective, especially during the prenatal period. Every dollar spent on smoking cessation interventions for a pregnant smoker saves $3 in neonatal costs and $6 in long term care costs for infants with disabilities caused from smoking.…”
mentioning
confidence: 99%
“…There are relatively large literatures that have examined smoking among women (Barker, Orleans, Halpin, & Barry, 2004; Cepeda-Benito, Reynoso, & Erath, 2004; Collins, et al, 2004; Patel, Bach, & Kris, 2004; Pauly, 2008; Reichert, Seltzer, Efferen, & Kohn, 2004; Schnoll, Patterson, & Lerman, 2007; Wetter, et al, 1999) and among African Americans (Brook, Saar, Zhang, & Brook, 2009; King, Polednak, Bendel, & Hovey, 1999; Lawrence, Graber, Mills, Meissner, & Warnecke, 2003; Moolchan, et al, 2007; Okuyemi, Pulvers, et al, 2007; Payne & Diefenbach, 2003; Pederson, Ahluwalia, Harris, & McGrady, 2000; Webb, 2008). Review articles on these topics have typically focused on differences between women and men without considering the concomitant role of ethnicity, or they have often focused on differences between African Americans and other ethnic groups without considering the role of gender [but see (Sanchez-Johnsen, 2005) for a review on smoking and obesity].…”
Section: Introductionmentioning
confidence: 99%